2004
DOI: 10.1038/sj.ejcn.1602038
|View full text |Cite
|
Sign up to set email alerts
|

Australian consumers are sceptical about but influenced by claims about fat on food labels

Abstract: Objectives: To explore the beliefs and attitudes of Australian consumers to claims about fat made on the labels of packaged food. Design: Content analysis of transcripts from focus group discussions. Subjects: A total of 26 female and 10 male participants aged 20-80 y, recruited by advertisement into six focus groups, stratified by age, sex and health status. Results: Awareness of claims about fat was high in this sample of Australians and participants admitted that they influenced their purchase decisions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 12 publications
5
69
0
1
Order By: Relevance
“…They indicated that claims such as 'low fat' for example, might prompt them to check the nutrition information provided on either front or back-of-pack for fat levels since many participants felt that these types of 'low' claims didn't offer sufficient detail to make a product choice and often invoked mistrust, a finding consistent with a number other studies on both nutrition and health claims (Chan, 2005;Mazis, 1997). Some participants even suggested that claims could be misconstrued as being targeted towards people with specific dietary needs and may therefore be discouraging for those outside the perceived target group.…”
Section: Nutrition Claimsmentioning
confidence: 60%
“…They indicated that claims such as 'low fat' for example, might prompt them to check the nutrition information provided on either front or back-of-pack for fat levels since many participants felt that these types of 'low' claims didn't offer sufficient detail to make a product choice and often invoked mistrust, a finding consistent with a number other studies on both nutrition and health claims (Chan, 2005;Mazis, 1997). Some participants even suggested that claims could be misconstrued as being targeted towards people with specific dietary needs and may therefore be discouraging for those outside the perceived target group.…”
Section: Nutrition Claimsmentioning
confidence: 60%
“…It was ranked 2 nd out of 10 foods in the Netherlands, versus 8 th in Australia. This may relate to the longer history of health claims on such foods in Europe (Wolfs et al, 2006) compared to Australia, where there is significant scepticism about claims on high fat foods (Chan et al, 2005). The fact that tea was rated the most attractive food carrier by Australian consumers may be influenced by the widespread presence of health claims on teas in the Australian market .…”
Section: Differences Between Australian and Dutch Consumersmentioning
confidence: 99%
“…The NIP can be confusing [19], especially for those with low literacy and numeracy skills [20], and is used infrequently [21][22][23]. Health claims are often regarded as a marketing tool [24,25] and consequently can be viewed with skepticism [26,27]. Reviews of the cognitive and affective effects of health claims conclude that they often induce a positivity bias.…”
Section: Nutrition Information On Food Packsmentioning
confidence: 99%